2020
DOI: 10.3171/2018.8.jns182029
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous sinus aneurysms: risk of growth over time and risk factors

Abstract: OBJECTIVECavernous internal carotid artery (ICA) aneurysms are frequently diagnosed incidentally and the benign natural history of these lesions is well known, but there is limited information assessing the risk of growth in untreated patients. The authors sought to assess and analyze risk factors in patients with cavernous ICA aneurysms and compare them to those of patients with intracranial berry aneurysms in other locations.METHODSData from consecutive patients who were diagnosed with a cavernous ICA aneury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…With recent technological advancements in neuroimaging, cavernous internal carotid artery (ICA) aneurysms are frequently diagnosed incidentally. 1) Most cavernous ICA aneurysms have benign natural histories, with low cumulative rates of rupture. 2) However, large (>15 mm) or giant (>25 mm) cavernous aneurysms may cause ophthalmoplegia, chemosis, ptosis, proptosis, visual changes, facial pain or numbness, and Horner’s syndrome (collectively called “cavernous sinus syndrome”) because of their mass effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With recent technological advancements in neuroimaging, cavernous internal carotid artery (ICA) aneurysms are frequently diagnosed incidentally. 1) Most cavernous ICA aneurysms have benign natural histories, with low cumulative rates of rupture. 2) However, large (>15 mm) or giant (>25 mm) cavernous aneurysms may cause ophthalmoplegia, chemosis, ptosis, proptosis, visual changes, facial pain or numbness, and Horner’s syndrome (collectively called “cavernous sinus syndrome”) because of their mass effect.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4) Moreover, recent literature reported that aneurysm size was a significant predictor of aneurysmal growth, and even asymptomatic large or giant aneurysms potentially present risks of new-onset symptoms. 1) Partial or complete thrombosis is not uncommon in such large/giant aneurysms, 5) and thromboembolic events caused by intra-aneurysmal thromboses have been also reported. 1) Although spontaneous intra-aneurysmal thrombosis involved parent artery thrombosis is rare and usually has good outcomes, some patients experience severe ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sidewall ICA aneurysms have comparatively low annual rupture risk of 0.2%, but account for nearly 40% of all aneurysm cases (21). Compared with other sites, ICA aneurysms have higher growth risk and tend to cause compression of surrounding tissues due to the proximity to cranial nerve or brain structures that make it difficult to perform surgical access at this location (22). So in this study, we selected two cases of sidewall ICA aneurysms, one of which had postoperative bleeding and the other had no postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…6 Nontraumatic CCAs are usually benign asymptomatic lesions, incidentally detected on imaging. 7 Symptoms caused by these aneurysms can be broadly divided into 2 types: compressive and vascular.…”
mentioning
confidence: 99%